2005
DOI: 10.1093/humrep/dei362
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality of 324 fertile Japanese men

Abstract: Japanese fertile men had a semen quality at the level of Danish men, who have been reported to have the lowest among investigated men in Europe. The low level of semen quality of the fertile Japanese men may be due to lifestyle or other environmental factors; however, ethnic differences caused by different genetic variation or combinations cannot be ruled out by this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
67
3
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 31 publications
9
67
3
7
Order By: Relevance
“…Regional differences in semen quality, possibly associated with environmental exposures or lifestyle, may explain this finding, as has been reported in Europe (33), the US (34), and Japan (35).…”
Section: Discussionsupporting
confidence: 69%
“…Regional differences in semen quality, possibly associated with environmental exposures or lifestyle, may explain this finding, as has been reported in Europe (33), the US (34), and Japan (35).…”
Section: Discussionsupporting
confidence: 69%
“…Kuriyama et al (2005) have reported that developmental exposure to a single low dose (60 µg/kg body weight) of 2,2′,4,4′,5-pentabromodiphenyl ether (PeBDE-99) decreased the sperm count in male Wistar rats. However, no previous studies have examined the relationship between human PBDE levels and sperm quality.We participated in an international project examining the sperm quality of fertile males and found that the sperm concentration of Japanese males was lower than that of European males (Iwamoto et al, 2006). The examination of sperm quality and an estimation of the concentration of chemicals in the serum would be required to reveal the correlation between chemical exposure and the sperm quality in Japanese males.…”
mentioning
confidence: 99%
“…Previous data from screened and general populations showed that there are obvious differences in semen quality between continents [6], countries [7] and even different areas in the same country [6,8,9]. Some of the studies also revealed temporal differences [10].…”
Section: Dear Editormentioning
confidence: 99%
“…Profound comments on this regard have been made and published in the Special Issue in Asian Journal of Andrology on "Semen analysis in 21st Century Medicine" in Issue 1 in 2010 [2][3][4][5]. In this letter, I would like to present some of my views and suggestions on reference limits of semen parameters.Previous data from screened and general populations showed that there are obvious differences in semen quality between continents [6], countries [7] and even different areas in the same country [6,8,9]. Some of the studies also revealed temporal differences [10].…”
mentioning
confidence: 99%